2021
DOI: 10.3390/ma14020239
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance Improvement of Cemented Tungsten Carbide Deep-Hole Drills after Ion Implantation

Abstract: The paper is dedicated to the life prolongation of the tools designed for deep-hole drilling. Among available methods, an ion implantation process was used to improve the durability of tungsten carbide (WC)-Co guide pads. Nitrogen fluencies of 3 × 1017 cm−2, 4 × 1017 cm−2 and 5 × 1017 cm−2 were applied, and scanning electron microscope (SEM) observations, energy dispersive spectroscopy (EDS) analyses, X-ray photoelectron spectroscopy (XPS) and Secondary Ion Mass Spectrometry (SIMS) measurements were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…One of such techniques is the ion implantation, a process that is widely used in many areas, e.g., semiconductor device fabrication or materials sciences in general [ 53 , 54 ]. It has recently been shown that implanting nitrogen ions into a cemented tungsten carbide guide pads for deep-hole drilling applications can substantially increase their hardness and durability [ 55 ]. These are also characteristic features of auxetic materials; however, the complicated mechanisms behind the changes of tribological, mechanical, and elastic properties of ion-implanted materials are not yet fully understood and explained.…”
Section: Introductionmentioning
confidence: 99%
“…One of such techniques is the ion implantation, a process that is widely used in many areas, e.g., semiconductor device fabrication or materials sciences in general [ 53 , 54 ]. It has recently been shown that implanting nitrogen ions into a cemented tungsten carbide guide pads for deep-hole drilling applications can substantially increase their hardness and durability [ 55 ]. These are also characteristic features of auxetic materials; however, the complicated mechanisms behind the changes of tribological, mechanical, and elastic properties of ion-implanted materials are not yet fully understood and explained.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, these processes are mostly applied for increasing stellites tribological, corrosion or erosion resistance, it should be emphasised that limited papers focus on the effect of stellites treatment on their CE resistance. Especially, ion implantation is one of the most promising anti-wear processes, which has a positive effect in a range of engineering applications such as corrosive [ 27 ] and sliding wear [ 26 , 28 ] performance of different metallic surfaces. Moreover, the investigation into the anti-cavitation application of different ion types and fluences into the metallic materials were discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, these processes are mostly applied for increasing stellites tribological, corrosion or erosion resistance, it should be emphasized that limited papers focus on the effect of stellites treatment on their CE resistance. Especially, ion implantation is one of the most promising anti-wear processes, which has a positive effect in the range of engineering applications such as corrosive [27] and sliding wear [26,28] performance of different metallic surfaces. Moreover, the investigation into the anti-cavitation application of different ion types and fluences into the metallic materials were discussed by the literature.…”
Section: Introductionmentioning
confidence: 99%